Checklist of earthworm species Annelida, Oligochaetain Algeria - Chergui, Chourouk Nebatti; Ouahrani, Nadjia Saidi; Pelosi, Celine (Zootaxa, 2025)
Earthworms are soil engineers that provide key functions and contribute to numerous ecosystem services including plant production. Little is known about the diversity, ecology, distribution and habitats of earthworm populations in Algeria. In this review article, all scientific studies on earthworms (Annelida, Oligochaeta) in Algeria were collected in order to provide a comprehensive inventory of knowledge on earthworm populations (i.e., occurrence, distribution and habitats) in the country. Among 24 studies and 346 earthworm sampling sites, a total of 40 earthworm species, 20 genera and 8 families (Lumbricidae, Acanthodrilidae, Criodrilidae, Glossoscolecidae, Haplotaxidae, Hormogastridae, Megascolecidae, Ocnerodrilidae) were recorded. The most frequently collected species were the endogeics Aporrectodea rosea and Aporrectodea caliginosa, with occurrences of 41% and 37%, respectively which could be misleading due to nomenclatorial issues. The species were mostly found in arable lands although listed in a wide range of habitats. Arable lands were the most frequently sampled habitats (19% of the samples) in Algeria followed by inland water borders (11%). This exhaustive review of the literature may be used as a basis for further monitoring studies of earthworm diversity and abundance under different land uses and climate zones in Algeria.